Communicating the Dangers of Illegal Migration: A Mixed Impact of Japa Syndrome on South-South, Nigeria - Guanah, Jammy Seigha (The Journal of Society and Media, 2025)
This paper explored the communication dynamics surrounding migration from Nigeria, popularly referred to as Japa syndrome, especially from the South-South region of the country, where some residents engage in illegal migration. The study investigated the information sources, awareness level, and potential for deterrence of danger-related messaging among regional residents. This study utilizes Knowledge Gap and Agenda Setting theories to analyze the risks of illegal migration. Knowledge Gap theory suggests that access to information varies among groups, impacting their views and decisions. Concurrently, agenda-setting theory highlights how media shapes public opinion and government responses by focusing on dangers, impacts, and root causes of migration. Data collected from questionnaires and a Question Guide indicates that residents primarily obtain migration information through social media, TV, radio, films, friends, and newspapers. Despite high awareness of the dangers of illegal migration, this didn't significantly deter residents from considering such journeys. It’s recommended that media messages about migration should be clearer and include not only the risks but also the underlying causes of migration aspirations and tangible alternatives. Comprehensive communication strategies should address both the dangers and motivations behind illegal migration.